Analisis strategi pengembangan pada koperasi produsen Andamel Mulyo Abadi Kota Batu - Mauliddin, Ahmad Fajar; Sumanto, Agus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Cooperative is a business entity that is owned and managed by its members with the principle of mutual cooperation. With the principle of kinship, cooperatives have the potential to help the community's economy. Cooperative data in Batu City shows that there are only 20 producer cooperatives out of a total of 208 cooperatives. The purpose of this research is to analyze so that it can find the right strategy in the development of the Andamel Producer Cooperative in order to survive and be able to compete with other competitors such as home-scale producers who have more numbers. This research uses descriptive quantitative method with IE and QSPM matrix analysis tools. The data obtained in this study are primary and secondary data. Primary data is obtained through interviews with informants, while secondary data is obtained from literature, journals, books, or other articles related to the topic of discussion. The results of the IE matrix show that the cooperative is in chart V where the point of a company is in the Hold and Maintenance position. Then, the results of the QSPM matrix found 3 alternative strategies that were prioritized, namely: 1. Maintaining product quality and standardization, 2. Empowering the younger generation to find innovations for cooperatives, 3. Innovation that focuses on customer service.